The Analysis of Deixis in the Novel Maryam by Okky Madasari - Anwar, Wulandari; Arianto, Arianto (LUMBUNG AKSARA, 2022)
This study aims to determine the elements of deixis in the literary work of the novel contained in the novel Maryam by Okky Madasari. This research focuses on finding the elements of place deixis, time deixis, and social deixis in Okky Madasari's Maryam novel. The main problem under study is to reveal the types and forms of deixis in detail in pragmatic studies. In this study, qualitative research methods are used, namely in the form of describing sentences resulting from data analysis in the form of sentences in novel conversations that have been analyzed in deixis elements. The results of this study found 184 deixis data consisting of 57 place deixis, 50 time deixis, and 77 social deixis. Examples of deixis words found are place deixis such as: there, this island, this village, in a big city and in front, then time deixis such as: now, then, later, long ago and yesterday, and social deixis such as: People Outside, Ahmadi, Imam, Merarig, and Pak Haji.